A Descriptive Investigation of the Prevalence of Neurological Disorders in People Treated Hemodialysis for End-Stage Renal Disease - Saad Hanan, Waqas Sardar, Raza Muhammad Khan, Abdul Haseeb, Sajjad Ali Khan, Muhammad Younas Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: Patients with end-stage renal disease (ESRD) who were receiving hemodialysis were the subjects of a study to determine the neurological effects of the treatment. Methodology: ESRD patients at the Institute of kidney diseases hayatabad peshawar were the subjects of this descriptive research, which ran from jan to Dec 2021. Before participating in the trial, all Chronic Kidney Disease (CKD) patients had been on Hemodialysis (HD) for at least six months. HD patients were monitored for a total of six months in this study. Neurological events were observed and recorded at this period. All patients on HD, regardless of gender or age, were included in this research, which was conducted between the ages of 17 and 77. In this research, patients under the age of 15 years, those with acute renal failure, congestive cardiac failure, cirrhosis of the liver, malignancy, disseminated intravascular coagulation, sepsis, meningitis, or encephalitis, were all ruled out as candidates for inclusion. The data was analysed using SPSS version 2.2. Results: Intradialytic hypotension, Cerebrovascular accident, Encephalopathy, Dialysis dementia, Neuropathy, Dialysis disequilibrium, Reversible leukoencephalopathy, Central pontine myelinosis, Autonomic dysfunction, and Myopathy were the most common neurological consequences. Conclusions: Our patients on hemodialysis suffer from the most prevalent neurological complication: Intradialytic hypotension. While the long-term result and prognosis of this group may be affected by cerebrovascular illnesses and Dialysis dementias, it is important to examine them as soon as possible. Keywords: neurological problems, (ESRD),frequency, hemodialysis , end-stage renal disease.